Ethanol to Aromatics on Modified H-ZSM-5 Part I: Interdependent Dealumination Actions - Seifert, Markus; Marschall, Mathias S.; Gille, Torsten; Jonscher, Clemens; Busse, Oliver; Paasch, Silvia; Brunner, Eike; Reschetilowski, Wladimir; Weigand, Jan J. (ChemCatChem, 2020)
In this study a H-ZSM-5 zeolite (Si/Al=11) was modified by a stepwise treatment with steam, sodium hydroxide and hydrochloric acid. During progressing dealumination by various treatment methods, the drawbacks of initial post-synthetic steps, e. g. pore-filling by steam dealumination, are compensated by subsequent steps, e. g. washing by acid, which leads to a scientifically based preparation of required ZSM-5 zeolite. Solid-state properties of as-synthesized and modified zeolites are determined by structural (XRD, ICP-OES, NMR), textural (physisorption, laser scattering) and acid sites analysis (TPAD). Consequently, extended dealumination without structural damage is demonstrated. Its origin by framework dealumination and pore cleaning is verified in ethanol to hydrocarbon process (ETH) by shape-selective formation of coke and aromatics, characterized by “aromatics index” (AI).
CRIS-Team Scopus Importer:2022-04-14
Keywords: aromatics index; ETH process; heterogeneous catalysis; post-synthesis; structure-activity relationships; synthesis design; zeolites